منظور زمن المستقبل وعلاقته بالإرتياح النفسي على ضوء بعض المتغيرات الشخصية - قطاب، نور الدين; زقاوة، أحمد عابد (جامعة قاصدي مرباح - مخبر تطوير الممارسات النفسية والتربوية, 2024)
هدفت الدراسة إلى الكشف عن العلاقة بين منظور زمن المستقبل والارتياح النفسي على ضوء الجنس والمستوى التعليمي، تم تطبيق مقياس منظور زمن المستقبل (البارقي، 2010) ومقياس الارتياح النفسي لكومنز (Communs, 2003) على عينة من (103) من طلاب المرحلة الثانوية والجامعية. توصلت النتائج إلى وجود علاقة ارتباطية موجبة بين منظور زمن المستقبل والارتياح النفسي لدى عينة الدراسة، كما وجدت فروق دالة على مقياس منظور زمن المستقبل لدى العينة تعزى إلى الجنس لصالح الإناث في الدرجة الكلية وبعد التوجه نحو المستقبل، في حين لم تكن هناك فروق دالة تعزى إلى متغير المستوى التعليمي. The study aimed at revealing the relationship between the future time perspective and subjective wellbeing in the light of gender and educational level. The future time perspective scale (Al-bareki, 2010) and the subjective wellbeing (Communs, 2003) were applied on a sample of (103) high school and university students. The results reached a positive correlation between the Future Time perspective and subjective wellbeing. There were also significant differences on the scale of the future time perspective in the sample due to gender in favour of females in the overall degree and after heading towards the future whereas there were no significant differences attributable to the variable educational level.
Keywords: السلوكيات الإنسانية -- الهدوء النفسي -- طلبة الجامعات